Mobilization of plant genetic resources from Bangladesh, Pakistan and Bhutan - N. P. Loskutova; T. M. Ozerskaya (Труды по прикладной ботанике, генетике и селекции)
The article covers the issues of plant genetic resources mobilization to the VIR collection from the territories of Pakistan, Bangladesh (until 1947, British India), and Bhutan as a result of collection missions, seed requests, and germplasm exchange. Repeated expeditionary surveys of the territories of modern Pakistan and Bangladesh resumed in the postwar period. In total, from 1971 to 1979 three expeditions were launched: in 1971 and 1978 to Pakistan, and in 1979 to Bangladesh. The first and the only expedition was sent to Bhutan in 1989. As a result, 2911 plant samples were collected and delivered to the Vavilov Institute. Among the collected plant materials, the most numerous were samples of groat crops (885), industrial crops (554), vegetables (517), and cereals (463). In addition to direct collecting, the Institute was constantly ordering plant germplasm through mail requests. There was no inflow of germplasm from Bhutan either in the prewar period or from 1946 to 2019. From Pakistan 338 samples were received, mostly through the USSR Ministry of Agriculture. Only 28 accessions were added to the Institute’s collection from Bangladesh. In total, over the entire period of the Institute’s existence, the total amount of germplasm mobilized from Bangladesh, Pakistan and Bhutan amounted to 3277 accessions, representing 130 plant species. Among them there were many landraces, wild species and crops wild relatives.